LncRNA EPR-induced METTL7A1 modulates target gene translation. Issue 13 (24th June 2022) - Briata, Paola; Caputo, Luca; Zapparoli, Ettore; Marcaccini, Elisa; Passalacqua, Mario; Brondolo, Lorenzo; Bordo, Domenico; Rossi, Annalisa; Nicoletti, Chiara; Bucci, Gabriele; Puri, Pier Lorenzo; Inga, Alberto; et al.
Abstract: EPR is a long non-coding RNA (lncRNA) that controls cell proliferation in mammary gland cells by regulating gene transcription. Here, we report on Mettl7a1 as a direct target of EPR . We show that EPR induces Mettl7a1 transcription by rewiring three-dimensional chromatin interactions at the Mettl7a1 locus. Our data indicate that METTL7A1 contributes to EPR -dependent inhibition of TGF-β signaling. METTL7A1 is absent in tumorigenic murine mammary gland cells and its human ortholog (METTL7A) is downregulated in breast cancers. Importantly, re-expression of METTL7A1 in 4T1 tumorigenic cells attenuates their transformation potential, with the putative methyltransferase activity of METTL7A1 being dispensable for its biological functions. We found that METTL7A1 localizes in the cytoplasm whereby it interacts with factors implicated in the early steps of mRNA translation, associates with ribosomes, and affects the levels of target proteins without altering mRNA abundance. Overall, our data indicates that METTL7A1—a transcriptional target of EPR —modulates translation of select transcripts.